Students’ mathematics self-efficacy in learning social arithmetic topic - Rama Nida Siregar; Didi Suryadi; Sufyani Prabawanto; Abdul Mujib (Institute of Advanced Engineering and Science, 2023)
The issue, the significance of student self-efficacy in the learning process, is what inspired this study. This study set out to identify and characterize students’ self-efficacy capacities for studying the social arithmetic topic in light of their unique traits. This research is descriptive research through questionnaire analysis using percentages. A self-efficacy questionnaire plus a questionnaire for students’ responses make up the tool used to assess self-efficacy abilities. In this study, the data were collected and evaluated using a Likert attitude scale to determine whether students’ self-efficacy in studying the social arithmetic topic had increased. The scale in this self-efficacy contains three components, namely students’ assessment of: i) the level of task difficulty (magnitude); ii) the variety of tasks (generality); and iii) the degree of stability in completing a task (strength) in social arithmetic topic. The conclusion obtained in this study related to self-efficacy in mathematics is that it can be seen as a whole in learning social arithmetic topic showing that there are 79.05% of students giving a positive response, meaning that almost all students assess themselves positively when learning social arithmetic topic.